Relative Sensitivity of Conventional Soybean to Three Dicamba Based Herbicides at Different Growth Stages - Knežević, Stevan (Acta herbologica, 2021)
Widespread use of dicamba-based herbicides such as Clarity® (dicamba diglycolamine salt, 480 g l-1), Engenia® (dicamba N,N-Bis-[3-aminopropyl] methylamine salt, 600 g l-1) and XtendiMax® (dicamba diglycolamine salt, 350 g l-1) with Vapor-Grip Technology for weed control in dicamba-tolerant (DT) crops have resulted in un-intended drifts, partly due to windy and common temperature inversions in many parts of United States. It is unclear if the dicamba-based herbicides made of different formulations or technologies have differential impact on sensitive soybeans including a conventional variety.  Thus, field studies were conducted in 2016 and 2017 to evaluate the relative sensitivity of a conventional soybean to micro-rates of three dicamba-based herbicide products (Clarity®, Engenia® and XtendiMax®) applied at three soybean growth stages (V2, V7/R1 and R2 stages). The dicamba micro-rates were 0, 0.56, 1.12, 5.6, 11.2, and 56 g ae ha-1; equivalent to 0, 1/1000, 1/500, 1/100, 1/50, 1/10 of the standard rate (560 g ae ha-1) respectively. The experimental design was a randomized complete block design in a split-split-plot arrangement with 4 replications. There was no significant difference in visual injury, growth or yield response of the conventional soybean to the three dicamba herbicides. The dicamba micro rates caused 40-80% visual injury and 0-97% yield loss depending on the growth stage of application. The estimated effective doses (ED values) suggested that conventional soybeans exposed to dicamba micro-rates at V7/R1 growth stage were more sensitive than those exposed at V2 and R2 growth stages. Based on the ED values, about 0.1% of dicamba standard rate was enough to cause 10% soybean yield loss when applied at V7/R1 stage; while about 1% of dicamba standard rate was required to cause the same level of yield loss when applied at V2 or R2 stage. By implication, dicamba drift on sensitive soybean plants should be avoided to prevent yield loss.